Improving Freight Forwarding Efficiency Through Digital Innovation, Regulation, And Infrastructure As Mediation - Sari, Mustika; Octaviani, Reni Dian; Nasution, Nursery Alfaridi (Dinasti Publisher, 2025)
The research aims discusses the impact of digital innovation, regulation, and infrastructure on operational efficiency in the freight forwarding industry in Indonesia freight forwarding industry. The study explores how technologies such as Track and Trace systems, IoT, and machine learning are transforming logistics by enhancing transparency and efficiency. However, challenges such as readiness, accessibility, and regulation hinder optimal digital adoption. The research uses the SEM-PLS method to analyze data from 150 logistics companies, revealing that digital innovation and regulation significantly influence operational efficiency, primarily mediated through infrastructure. Accessibility, while not directly impactful, strengthens infrastructure, which indirectly enhances efficiency. This study provides a comprehensive perspective on the enablers and barriers to digital adoption, offering useful policy and managerial implications for the logistics industry in Indonesia. The study concludes that digital innovations, supported by infrastructure development and regulations, are critical to improving the performance of logistics operations, particularly in the context of the digital economy.